Acknowledgement to Reviewers 2023 - Michał Tomczyk (Polskie Towarzystwo Farmaceutyczne, 2024)
We would like to take this opportunity to thank you for the effort and expertise that you contribute to reviewing, without which it would be impossible to maintain the high editorial standards of Acta Poloniae Pharmaceutica - Drug Research.